Revitalisasi Peran Dan Fungsi Penghulu: Upaya Meminimalisir Pernikahan Dini Di Kabupaten Nganjuk - Imam Mahmud (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
This study aims to analyze how social media can affect the lives of adolescents in Nganjuk district and the role of what can be done by religious leader in minimizing the high number of early marriage in Nganjuk regency. This study uses a descriptive qualitative research method, with data retrieval techniques through obesrvasi and Library Studies, and Forum Group Discussion (FGD). The results of this study indicate that the average annually cases of early marriage in Nganjuk district reached 90 cases, the average still in childhood. While relating to the role of penghulu in minimizing early marriage, there are at least four roles that can be done by penghulu; 1) Increase the scope of educational and other support services for girls between the ages of 15 and 17 years. 2) Addressing social and cultural norms at the local level. 3) Create more opportunities for girls to access higher education and economic skills training. 4) Provide skills of using gadgets for productive activities.